A new species of the Andean genus Leptopeltus Bernhauer (Coleoptera: Staphylinidae: Staphylininae) with a revised key and an updated phylogeny - López-Prada, Manuel F.; Chani-Posse, Mariana Raquel (Zootaxa, 2020)
Leptopeltus trogloxenus López-Prada & Chani-Posse, a new species of the subtribe Philonthina (tribe Staphylinini) from the Andes of Colombia, is described and illustrated. A dataset of 49 morphological characters scored for 10 taxa, including all currently known species of Leptopeltus Bernhauer and its putative sister group, Leptopeltoides Chani-Posse & Asenjo, was prepared and analysed by maximum parsimony. Our analysis unambiguously placed L. trogloxenus within Leptopeltus in a sister-group relationship with a clade of four species. A revised key to species and an updated phylogeny of Leptopeltus are also provided.